(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
Ibuprofen-loaded Poly-(methyl vinyl ether-co-maleic anhydride) (PVM/MA) nanoparticles were successfully prepared by Solution-enhanced Dispersion by Supercritical CO_2 (SEDS). Ibuprofen and PVM/MA were first homogeneously dissolved in acetone, and then the resulting solution was simultaneously sprayed with supercritical CO_2 through a coaxial nozzle, forming ibuprofen-PVM/MA nanoparticles. FTIR spectra demonstrated that ibuprofen was successfully incorporated into PVM/MA and the SEDS process was a typically physical process. The absolute value of the zeta potential of the obtained ibuprofen-PVM/MA nanoparticles was larger than 40 mV, indicating a good stability of the nanoparticles in aqueous suspension and suitability for oral administration. Analysis of Thermogravimetry-differential Scanning Calorimetry (TG-DSC) revealed that the effect of the SEDS process on the thermostability of the drug and the coating polymer was negligible. The results of Gas Chromatography (GC) analysis confirmed that the SEDS process could efficiently remove the organic residue. The drug dosage of 20% corresponded to a final drug load of 5.3 ± 0.2%, which appeared to be relatively low and indicated that most of the ibuprofen was lost in the supercritical CO_2. Significant differences existed among the drug release profiles obtained from different release media; a medium with a low pH could efficiently prevent the release of ibuprofen from ibuprofen-PVM/MA nanoparticles, which works to reduce the adverse effects of ibuprofen on the stomach and makes ibuprofen-PVM/MA nanoparticles suitable for oral administration.